African-American Grandmothers: Does the Gender-Entrapment Theory Apply? Essay Response to Professor Beth Richie - Jessica Dixon Weaver (Washington University Journal of Law & Policy, 2011)
My focus is on the role of African-American grandmothers and the role that they play in the cycle of incarceration that is prevalent in poor black communities. The mass incarceration of African-American men and women has affected African-American families in monumental ways. In this Essay, I will primarily focus on: (1) the history of African-American grandmothers in the United States; (2) their status when they take on the role of raising grandchildren of their incarcerated children; and (3) the impact of mass female incarceration on these children. Finally, I will offer some possible solutions to reduce the impact on the families of African-American women caught in the gender entrapment cycle of crime and imprisonment.
Keywords: African American women; Domestic violence; Entrapment (Criminal law); Imprisonment; Women prisoners; United States